2011
DOI: 10.1038/emboj.2011.403
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of individual kinesin-5 Cin8 motors is modulated by loop 8, ionic strength and microtubule geometry

Abstract: Kinesin-5 motors fulfil essential roles in mitotic spindle morphogenesis and dynamics as slow, processive microtubule (MT) plus-end directed motors. The Saccharomyces cerevisiae kinesin-5 Cin8 was found, surprisingly, to switch directionality. Here, we have examined directionality using single-molecule fluorescence motility assays and live-cell microscopy. On spindles, Cin8 motors mostly moved slowly (∼25 nm/s) towards the midzone, but occasionally also faster (∼55 nm/s) towards the spindle poles. In vitro, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
215
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(245 citation statements)
references
References 65 publications
29
215
1
Order By: Relevance
“…There is also evidence of communication through the tetrameric coiled-coil domain meaning that mechanical activity of one pair of heads may regulate the behavior of the motors at the opposite end of the molecule (46). Additionally, this model provides open questions on the ionic strength-dependent directional switching of yeast kinesin Cin8 (47,48) and the microtubule depolymerizing properties of yeast kinesin-5 Kip1p (49,50). Finally, phosphorylation may regulate motor activity (51).…”
mentioning
confidence: 99%
“…There is also evidence of communication through the tetrameric coiled-coil domain meaning that mechanical activity of one pair of heads may regulate the behavior of the motors at the opposite end of the molecule (46). Additionally, this model provides open questions on the ionic strength-dependent directional switching of yeast kinesin Cin8 (47,48) and the microtubule depolymerizing properties of yeast kinesin-5 Kip1p (49,50). Finally, phosphorylation may regulate motor activity (51).…”
mentioning
confidence: 99%
“…At 3 nM ase1, the sliding velocity was 48% higher than in its absence (p<0.05). A similar decrease in velocity was reported for microtubule sliding by ScCin8 in cell extracts lacking Scase1 (Gerson-Gurwitz et al, 2011). Moreover, spindle elongation rates are lower in ase1∆ cells (Loïodice et al, 2005;Syrovatkina et al, 2013).…”
Section: Ase1 Increases and Decreases Sliding Velocity Depending On Isupporting
confidence: 83%
“…The velocity of gliding was slightly different for the two directions in our standard buffer containing MRB80 and 72mM KCl (1.17±0.33 µm/min; ±SE; N=37 for plus-end directed and 1.49±0.53 µm/ min; N =18 for minus-end directed gliding; p<0.05). Bidirectional gliding was earlier reported for kinesin-5 motors from budding and fission yeasts and similarly to ScCin8, we observed that minus-end-directed motion became more prevalent at higher ionic strength ( Figure 2C) (Gerson-Gurwitz et al, 2011;Roostalu et al, 2011;Fridman et al, 2013;Edamatsu, 2014). Because recombinant N-and C-terminal fusions of GFP and klp9 were not motile we could not simply establish whether individual klp9 motors moved towards microtubule minus-ends like other kinesin-5 motors from yeasts.…”
Section: Klp9 Is a Bidirectional Motormentioning
confidence: 58%
See 2 more Smart Citations